2010
DOI: 10.1186/1471-2377-10-48
|View full text |Cite
|
Sign up to set email alerts
|

Generic quality of life assessment in dementia patients: a prospective cohort study

Abstract: BackgroundQuality of life (QoL) is increasingly used to characterize the impact of disease and the efficacy of interventions.MethodsProspective cohort study in patients' and proxies' homes with137 patients with dementia (age 52 to 88; Mini-Mental Status Examination (MMSE) 3 to 28) and their proxies (age 43 to 90). MMSE, Behave-AD, Geriatric Depression Scale (GDS), and Bayer-ADL scale (B-ADL), and the Euroqol (EQ-5D; patient self-rating, proxy self-rating, and proxy-rating of patient).ResultsB-ADL impairment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 34 publications
0
50
0
1
Order By: Relevance
“…Generally speaking, previous studies have also reported an association between caregiver depression and more negative assessments of the patient's functional capacities, 1 neuropsychiatric symptoms, 6 and quality of life. [19][20][21][22][23][24][25][26] Caregiver gender had less of an influence than both burden and depression. In general, however, women, and especially daughters, gave more negative assessments of the patient's capacities.…”
Section: Influence Of Caregiver Factors On Patient Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, previous studies have also reported an association between caregiver depression and more negative assessments of the patient's functional capacities, 1 neuropsychiatric symptoms, 6 and quality of life. [19][20][21][22][23][24][25][26] Caregiver gender had less of an influence than both burden and depression. In general, however, women, and especially daughters, gave more negative assessments of the patient's capacities.…”
Section: Influence Of Caregiver Factors On Patient Assessmentsmentioning
confidence: 99%
“…14,15 The caregiver's evaluation may also be influenced by variables such as personality, general well-being, and the quality of relationship with the patient, and these factors may also produce a degree of bias in caregiver assessments. 16 When it comes to evaluating the patient's quality of life (QoL-p), both burden [17][18][19][20][21][22] and depression [19][20][21][22][23][24] in caregivers have been shown to produce a negative bias in their assessments. Likewise, burden and poor mental health in caregivers are inversely correlated with their perception of QoL-p 25,26 ; female caregivers give the most negative ratings of QoL-p, 17,27 and they also present with more depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…The observed stability in patients' ratings of QoLp (39, 40) and the decreasing ratings among caregivers has been widely reported. (13,20) …”
Section: Severity Of Dementia and Patients' Quality Of Lifementioning
confidence: 99%
“…(AD) This research has shown that in patients higher depression scores, (2-4) the presence of behavioral disorders (5-7) and greater functional deficits (8,9) all have negative effects on QoLp. Among caregivers, poorer ratings of QoLp have been shown to be associated with functional deficits (10,11) and behavioral disorders (3,9) in the patient and with burden (3) and depression (12,13) in the caregiver. Some authors have also reported that perceptions of QoLp are affected by sociodemographic and contextual factors such as the caregiver's gender (14), his or her relationship to the patient, (15)(16)(17)) the patient's place of residence (2,3) or the environmental conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation